MENGHITUNG SPECIFIC FUEL CONSUMPTION (SFC) PADA ALAT ROTARY KILN DI PABRIK II PT SEMEN BATURAJA TBK - Nurfatihah, Yasyifa; Safaruddin, Safaruddin; Muzzaki, Mukti Mabrur (PHENOMENON : Multidisciplinary Journal Of Sciences and Research, 2023)
PT Semen Baturaja Tbk. as one of the largest cement industries on the island of Sumatra uses a rotary kiln in its production process. Rotary kiln in the cement industry has an important role because it will determine the quality of the product. Rotary kiln serves as a place to react raw materials to become products. The type of coal used as fuel for the rotary kiln is BA-45 coal. This type of coal was chosen because it has a calorific value of 4,500 kcal/kg. The calculation of SFC in the rotary kiln aims to determine how much fuel is needed in the combustion process in the rotary kiln. This calculation is based on actual data taken from the Central Control Room (CCR) and the Quality Control (QC) laboratory. The average SFC calculation was obtained at 619,658 Kcal/kg. The largest SFC value was on July 22, 2023, which was 676.71 kcal/kg, while the smallest SFC was obtained on July 20, 2023, which was 568.54 kcal/kg. The high and low SFC obtained is influenced by many factors, such as the amount of kiln feed, water content in the feed, and the type of coal used.